2008
DOI: 10.1007/s10529-008-9714-5
|View full text |Cite
|
Sign up to set email alerts
|

Expression and secretion of recombinant ZZ–EGFP fusion protein by the methylotrophic yeast Pichia pastoris

Abstract: We constructed a fusion protein ZZ-EGFP by fusing the ZZ domains of staphylococcal protein A (SpA) and enhanced green fluorescent protein (EGFP). ZZ-EGFP was secreted in the yeast, Pichia pastoris, with a hexahistidine tag. Its expression level was determined by measuring the fluorescence of EGFP. When the recombinant yeast cells in shake-flasks were induced with 0.5% methanol for 96 h, a maximum yield of 115 mg ZZ-EGFP/l was obtained. The resulting ZZ-EGFP fusion protein retained immunoglobulin G (IgG)-bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Control experiments such as SDS-PAGE, Western blot, or other immunochemical analysis proved that the integrity of the fusion protein is generally of great importance when using EGFP as a fusion tag. Using these additional analyses, some other authors observed no cleavage of a GFP fusion protein (Surribas et al 2006(Surribas et al , 2007Tang et al 2008;Sjöblom et al 2012), indicating that the cleavage we observed is likely to be product-specific.…”
Section: Egfp Was Cleaved From Porcine Trypsinogenmentioning
confidence: 45%
“…Control experiments such as SDS-PAGE, Western blot, or other immunochemical analysis proved that the integrity of the fusion protein is generally of great importance when using EGFP as a fusion tag. Using these additional analyses, some other authors observed no cleavage of a GFP fusion protein (Surribas et al 2006(Surribas et al , 2007Tang et al 2008;Sjöblom et al 2012), indicating that the cleavage we observed is likely to be product-specific.…”
Section: Egfp Was Cleaved From Porcine Trypsinogenmentioning
confidence: 45%
“…In this respect, eGFP fusion proteins may be used with caution when investigating secretory processes in P. pastoris . However, these effects may also be protein dependent, as there were cases reported where GFP was successfully used to evaluate signal sequences [ 59 , 60 ] and some GFP fusion proteins were sufficiently secreted [ 61 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many IG-binding proteins have been widely studied and used in the fields of immunology and biotechnology (Dahlbom et al 2008), the most well known examples are staphylococcal protein A (SPA) and ZZ domains (two synthetic IgG-Fc-fragment-binding domains based on the sequence of the domain B of SPA) (Moks et al 1986;Ståhl and Nygren 1997). So far, SPA and ZZ domains fused with GFP or its variants have been developed in Escherichia coli or yeast for recombinant immunoconjugates (Aoki et al 1999;Fujino et al 2002;Huang et al 2006;Tang et al 2008). However, their applications mostly focus on Western blotting.…”
Section: Introductionmentioning
confidence: 99%